Techno-Da'i and The Qur’anic Based Social Integration Building - Nur Arfiyah Febriani; Zaenuddin Hudi Prasojo; Badru Tamam (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Modern society tends to be techno-centric. Technology removes geographical distance and other physical restrictions in communication. Therefore, this matter must be responded by the preachers to reach the "e-society" mad'u with the world without limits. This has become a challenge as well as an opportunity for the da'is, and now they must be ICT literate. Ironically, the phenomenon of freedom of expression leads to acts of radicalism both in cyberspace and the real world that threaten the social integration of the world community. Here is the importance, how can techno-da'is influence e-society so that in theirexpression theystill uphold Islamic values that prioritize security, peace, safety, happiness and harmony among humans as described in the Qur’an. The strategies of "Normative Integration" revealed from the Quran consist of several phases, namely: accommodation, cooperation, coordination, assimilation, progressiveness and submissive-repentance.[Masyarakat modern cenderung teknosentris. Teknologi menghapus jarak geografis dan keterbatasan fisik manusia lainnya dalam berkomunikasi. Hal ini harus direspon oleh para da'i untuk menjangkau mad'u “e-society” dengan dunia tanpa batasnya. Hal ini menjadi tantangan sekaligus peluang bari para da’i, da’i kini harus melek ICT. Ironisnya, fenomena kebebasan berekspresi berujung kepada tindakan radikalisme baik di dunia maya dan dunia nyata yang mengancam integrasi sosial masyarakat dunia. Di sinilah pentingnya, bagaimana seorang tekno-da’i mampu mempengaruhi e-society agar dalam berekspresi tetap menjunjung nilai-nilai Islami yang sangat mendahulukan keamanan, kedamaian, keselamatan, kebahagiaan dan keharmonisan antar umat manusia sebagaimana deskripsi di dalam al-Quran. Strategi “Integrasi Normatif” yang dapat diungkap dari al-Quran terdiri dari beberapa fase, yaitu: akomodasi, kerjasama, koordinasi, asimilasi, progresif dan submisif-repentansi.]